PENINGKATAN KONDISI FISIK ATLET POPB SKI AIR DAN WAKEBOARD JAKARTA TAHUN 2026 - Maslikah, Uzizatun; Fachrezzy, Fahmy; Hermawan, Iwan; Ali, Masnur; Citrasari, Viranti; Nurcahya, Arga (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Physical condition is a fundamental determinant of success in water ski and wakeboard athletes, as it directly influences athletic performance and reduces the risk of injury during training and competition. Preliminary assessments of athletes participating in the 2026 Jakarta Continuous Sports Development Program (POPB) for Water Ski and Wakeboard indicated that several physical fitness components, including muscular strength, endurance, balance, agility, and core stability, had not yet reached optimal levels, highlighting the need for a structured and evidence-based physical training program. This study aimed to analyze improvements in the physical condition of POPB Water Ski and Wakeboard athletes following the implementation of a systematic physical training program. A quantitative approach with a one-group pretest–posttest design was employed. The participants were POPB Water Ski and Wakeboard athletes who completed the entire training program. Physical condition was assessed before and after the intervention using a battery of tests measuring muscular strength, endurance, agility, balance, flexibility, and core stability. The collected data were analyzed using descriptive and inferential statistics to determine changes in physical condition after the intervention. The results demonstrated improvements across all measured physical fitness components, with the greatest gains observed in muscular strength, balance, and core stability. These findings indicate that a structured, progressive, and sport-specific physical training program is effective in enhancing the physical readiness of POPB Water Ski and Wakeboard athletes. Therefore, this training model can be recommended as an evidence-based approach to support long-term athlete development and optimize competitive performance.